REVIEW OF THE NEWLY PUBLISHED MONOGRAPH ON OSMAN PAZVANTOĞLU’S LIBRARY IN VIDIN AND ITS PUBLISHED CATALOGUE - Gabriela Angelova (Издател)
This review focuses on the recently published monograph by Prof. Stoyanka Kenderova. The book provides insights into the history, thematic scope, and the catalogue of the Vidin Vakuf Library (1837–1887) established by Osman Pazvantoğlu. The work represents a logical progression of an enduring interest in the subject and offers significant contributions to the realm of Ottoman studies and the history of vakuf libraries within the Bulgarian territories of the Ottoman Empire.